Integration of Entrepreneurship in Tribal Communities: An Analytical Study of Tribal Economy Propensity, Cultural distinctiveness, and Policy framework in Postmodern Bharat (India) - Shirsath, Shyam T.; Kumare, Swapnil S. (PT Global Digital Sains Tekno, 2025)
Purpose: This study investigates the evolving landscape of tribal entrepreneurship in post-liberalization India, with a focus on how indigenous communities mobilize enterprise as a form of economic self-determination, cultural resilience, and ecological stewardship. The purpose is to critically examine the intersection of tribal identity, policy frameworks, and entrepreneurial ecosystems, highlighting both opportunities and systemic constraints. Method: This research employs a qualitative-descriptive approach, drawing on secondary data from government reports (NITI Aayog, Ministry of Tribal Affairs, TRIFED), academic literature, and policy evaluations. It utilizes a multidimensional analytical framework encompassing structural, cultural, and policy lenses to assess the effectiveness of central schemes such as Van Dhan Yojana, TRIFED, and Stand-Up India. Findings: The findings reveal that while these initiatives have expanded tribal participation in enterprise, significant gaps persist in fund utilization, skill development, and market integration. Challenges include historical land alienation, institutional exclusion, and deficits in culturally relevant education. Moreover, the lack of decentralized governance and real-time monitoring mechanisms undermines the sustainability of tribal ventures. Implication: The study’s implications are twofold: it calls for embedding entrepreneurial education within tribal skilling ecosystems and promoting women-led cooperative models, while also advocating for a Van Dhan Innovation Challenge to incubate tribal startups. These recommendations aim to reorient policy toward participatory, culturally embedded development. Originality: The originality of this research lies in its framing of tribal entrepreneurship not merely as economic activity but as a site of cultural negotiation and systemic transformation—offering a nuanced lens for future policy and practice.